2016
DOI: 10.1103/physrevlett.116.198001
|View full text |Cite
|
Sign up to set email alerts
|

Complex Contact-Based Dynamics of Microsphere Monolayers Revealed by Resonant Attenuation of Surface Acoustic Waves

Abstract: Contact-based vibrations play an essential role in the dynamics of granular materials. Significant insights into vibrational granular dynamics have previously been obtained with reduced-dimensional systems containing macroscale particles. We study contact-based vibrations of a two-dimensional monolayer of micron-sized spheres on a solid substrate that forms a microscale granular crystal. Measurements of the resonant attenuation of laser-generated surface acoustic waves reveal three collective vibrational modes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 43 publications
7
77
0
Order By: Relevance
“…The mode labeled V corresponding to the most prominent peak in the spectra, as shown in Fig. 2(e), was previously identified as the vertical contact resonance mode [7,9,10]. Figure 2(e) also shows small peaks to either side of the V-mode peak which we assigned to horizontal-rotational modes labeled HR and RH following Ref.…”
Section: B Experimentsmentioning
confidence: 59%
See 4 more Smart Citations
“…The mode labeled V corresponding to the most prominent peak in the spectra, as shown in Fig. 2(e), was previously identified as the vertical contact resonance mode [7,9,10]. Figure 2(e) also shows small peaks to either side of the V-mode peak which we assigned to horizontal-rotational modes labeled HR and RH following Ref.…”
Section: B Experimentsmentioning
confidence: 59%
“…In these initial studies, the observed phenomena, such as an avoided crossing in the Rayleigh SAW dispersion [7] and the resonant attenuation of SAWs by microspheres [9], could be well accounted for by a simple model where microspheres did not interact with each other [7]. Refined measurements of the resonant attenuation of SAWs * avegaflick@gmail.com † maznev@mit.edu revealed horizontal-rotational modes enabled by interparticle interactions [10]. However, none of the experiments performed on self-assembled microgranular monolayers were done on a "single-crystal" sample with long-range order extending over distances comparable to the measurement spot size.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations